Various Lifestyle Factors of Flight Crew Members - Marta Bon; Maja Pori; Tanja Kajtna (Karolinum Press, 2015)
Various Lifestyle Factors of Flight Crew Members The main aim of the research was to analyze certain lifestyle factors of flight crew members. This profession has rather high demands relating to body type, basic skills, as well as good mental and physical condition. The sample of respondents included 76 members of the Adria Airways d. d. cabin crew (19.7% men and 80.3% women) with the average age of 30.3 years (SD = 9.88), most of them (74.1%) finished high school and only one third had a full-time work contract. Using a questionnaire, we investigated the amount of exercise they get during work and in their free time, as well as their health conditions. Results show that in their free time most of the respondents participate in sports, with outdoor sports being the most popular form of exercise (running and walking, hiking, skiing, and swimming). The respondents spend most of their time at work standing up (18.4%) and walking (27.6%). Many of them (35%) find that they have to maintain postures that are uncomfortable. Most of them experience a combination of all the above. Most (38.2%) do sports at least twice a week, and as many as 84.2% 3 to 5 times a week. Only 4% of the respondents participate in sports activities organized by their employer. Most (77.6%) believe themselves to be in good health and only 6.6% believe themselves to be often under stress. Relatively many smoke. Among health problems, the highest percentage (46.1%) of respondents list fatigue, followed by back pain (34.2%) and neck pain (30.3%). Considering the characteristics of this profession, we recommend cabin crew members do aerobic exercise as well as more complex and preventative sport exercises intended to prevent back pain, and also to do more exercises for strength, core stability and flexibility. Různé faktory životního stylu členů letové posádky Hlavním cílem výzkumu bylo analyzovat některé faktory životního stylu členů letových posádek. Tato profese klade vysoké nároky na tělesnou konstituci, základní dovednosti, dobrou psychickou a fyzickou kondici. Vzorek respondentů byl složen ze 76 členů Adria Airways - palubních průvodčích (19,7 % mužů a 80,3 % žen) s věkovým průměrem 30,3 let (SD = 9,88). Většina z nich (74,1 %) dokončila střední školu. Pouze jedna třetina měla pracovní smlouvu na plný úvazek. Pomocí dotazníku byla zjišťována frekvence cvičení, které respondenti provádějí v práci a ve svém volném čase, a jejich zdravotní stav. Výsledky dokumentují, že ve volném čase se většina respondentů účastní sportů v přírodě (běh, chůze, turistika, lyžování, plavání). Většinu času v práci tráví respondenti ve stoje (18,4 %) a při chůzi (27,6 %). Mnoho respondentů (35 %) si uvědomuje, že musí vydržet v pozicích, které jsou nepříjemné. Většina z nich zažívá kombinaci předchozího. Mnozí (38,2 %) sportují alespoň dvakrát týdně, 84,2 % uvádí 3-5krát týdně. Pouze 4 % respondentů se účastní sportovních aktivit organizovaných zaměstnavatelem. Většina vyšetřovaných (77,6 %) se domnívá, že jsou v dobrém zdravotním stavu, pouze někteří (6,6 %) jsou přesvědčeni, že se často nacházejí pod tlakem. Poměrně mnoho respondentů kouří. Ze zdravotních problémů jsou v nejvyšší míře uváděny únava (46,1 %), bolesti zad (34,2 %) a bolesti krční páteře (30,3 %). S ohledem na charakteristiky této profese doporučujeme palubním průvodčím provádět zejména aerobní cvičení, ale i složitější preventivní pohybová cvičení, jejichž cílem je především prevence bolesti zad. Dále by měli provádět cvičení zaměřená na rozvoj síly a rovněž cvičení orientovaná na základní stabilitu a flexibilitu.